Bibliometric data on 'grey literature' in the archaeological report genre - Börjesson, Lisa (Uppsala University, 2016)
The study in which this data was collected aimed at nuancing the perception about professional documentation (a.k.a. ‘grey literature’), assuming perception of documentation being a cultural aspect of accessibility. It explores variations within the archaeological report genre through a bibliometric analysis of source use. Source characteristics are explored as well as correlations between report authors and source originators. Statistical frequency distribution is complemented by a correspondence analysis and a k-Means cluster analysis to explore patterns. The patterns are interpreted as ‘frames of references’ and related to circumstances for archaeological work.

The study focused on Swedish field evaluation reports.

The dataset was originally published in DiVA and moved to SND in 2024.

Se engelsk version av katalogposten för beskrivning av data.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Bibliometric data on 'grey literature' in the archaeological report genre
Data files for journal article Grey literature – grey sources? Nuancing the perception of professional documentation: the case of Swedish archaeology
Keywords: archaeology; arkeologi; grey literature; grå litteratur; Library and Information Science; Biblioteks- och informationsvetenskap; Information Studies; Biblioteks- och informationsvetenskap